Effect Of Body Condition-Score On Serum Biochemical Profile And Body Morphometry In Crossbred Dairy Cattle (Applied Biological Research, 2017)
A study was conducted to investigate association of body condition-score  (BCS) with serum biochemical profile and body morphometry of cross bred cows. Crossbred cows of same parity were selected randomly and  grouped into three categories of 6 animals each, based on body condition  score (BCS) [2-3 (A), 3-4 (B) and >4 (C)] at MLRI, Mansbal (Kashmir).  Blood samples were collected from these animals at 5 stages viz., 15 days  prepartum (stage I); and 5th day (stage II), 15th day (stage III), 30th day  (stage IV) and 45th day (stage V) postpartum. Highest BCS was observed  at stage I in all the groups and lowest at stage IV in group A and stage V  in groups B and C. Serum glucose was highest at stage I in all the groups  but significantly decreased at stage II. Serum urea showed highest value  at stage IV. Total protein and albumin contents in all groups increased  with progress of lactation. Total cholesterol was lowest at stage I in  group B and C and at stage II in group A. Body length didn’t differ  among the various BCS groups. Chest girth and pelvic girth varied  significantly within BCS groups with highest values of BCS in group C.
Keywords: Body condition score; crossbred cattle; morphometry; serum biochemistry